Characteristics and distribution of geohazards since the middle miocene of the Xisha sea area, South China Sea - Zhou, Jiao; Chen, Hongjun; Chen, Jiale; Yi, Shantang; Guo, Lihua; Hu, Xiaosan; Du, Wenbo; Sun, Meijing (Frontiers in Earth Science, 2023)
Geological hazards can cause significant harm to the construction and maintenance of reef infrastructure projects in the Xisha Sea area. This study uses high-resolution multichannel earthquake data, single-channel seismic profiles, and multi-beam survey data to identify and analyze the geological hazards in the Xisha Sea area since the Miocene. Based on the geophysical data interpretation, the destructive geological disaster factors that are active, such as active faults, shallow gas, diapers, landslides, multistage scarps (steps), scouring troughs, and canyons, as well as the restrictive geological disaster factors without activity ability, such as buried paleochannels, pockmarks, reefs, and undersea volcanoes, are identified and analyzed. This paper discusses the causes and hazards of geological hazards and, for the first time, draws a comprehensive plane layout of the geological hazards. The above analysis demonstrates that the scarps are mainly located around the atolls or platforms, and the slope of the southeast seabed topography is significantly higher than that of the northwest. There are 7 medium and large landslides, mainly located around Yongxing Plateau and Yongle Plateau, caused by gravity and faulting. Shallow gas is mainly developed in the southern part of the North Reef and is indicated by diaper structures, faults, and gas chimneys. A series of shallow faults are developed in the study area, mainly steep normal faults. The scouring troughs are primarily distributed near the Yongxing Platform, Zhongjian North Platform, and Huaguang Platform. Submarine canyons are primarily located in the northern and southern parts of the Shidao Platform. Affected by multiple factors such as hydrodynamic conditions, the stability of sedimentary layers, and sediment supply, the scour degree varies, with the general depth ranging from several meters to several hundred meters. Underwater infrastructure in the study area should not be constructed in areas with active and destructive geological hazards. The results of this study can serve as a guide for further exploration in the Xisha area and disaster prevention and mitigation during construction activity in the area.